SOSIALISASI DAN KUALITAS E-REGISTRATION TERHADAP TINGKAT KESADARAN WAJIB PAJAK ORANG PRIBADI - Puspita, Wike Churnia; Widyawati, Dini (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
Taxation are the contributions from the people to the state treasury under the law, so that it can be forced by not receiving remuneration directly. This research is aimed to find out how great the influence of the socialization and the quality of e-registration system can enhance the awareness of individual taxpayer to register himself in order to obtain NPWP. This research is quantitative which has been done by using descriptive methods. The data collection method has been done by issuing questionnaires. The research examination has been done by using multiple linear regressions, the collected data is in the form of interval data that uses one to five score measurement. The population is individual taxpayers in KPP Pratama Surabaya Gubeng and the sampling technique has been done by accidental sampling. The result of examination of R2 determination coefficient shows the contribution of quality and socialization of e-registration to the awareness level of individual taxpayers. This result is supported by the acquisition of correlation coefficient by 55% which shows the correlation among these variables to the awareness level of individual taxpayers. The result of the t test shows that the quality and the socialization of e-registration and has positive influence to the awareness level of individual taxpayers.Keywords: Socialization, e-registration quality, awareness level of individual taxpayer.